Comparison of E layer critical frequency over the Thai station Chumphon with IRI. Issue 8 (15th April 2015) - Wongcharoen, P.; Kenpankho, P.; Supnithi, P.; Ishii, M.; Tsugawa, T.
Abstract In this research, as a part of working towards improving the IRI over magnetic equatorial region, the critical frequency of E layer in the ionosphere (foE) derived from the ionogram at Chumphon station (10.72°N, 99.37°E), Thailand, during 2005–2008 is analyzed. The Chumphon station is located in the magnetic equatorial region at the magnetic latitude of 3.22°N. The seasonal variation of the foE measurements is compared to the IRI foE predictions with the optional input in the sunspot number (Rz12) and the solar radio noise flux (F10.7). For a declining phase of the solar cycle 23 during the year 2005–2008, the study shows that the IRI foE prediction is similar to the foE observation during the period of 2005–2008. The maximum differences between the IRI foE prediction and foE observation are about 500 kHz during daytime period of 2007.